1998
DOI: 10.1016/s1361-9209(97)00032-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the effects of driver variability on real-world vehicle emissions

Abstract: AbstractÐRecent studies on real-world automobile emissions measurements have not adequately addressed the question of whether driving style a ects emission levels. In this study, we hypothesized that given the same experimental conditions and a random selection of drivers, the variability associated with individual driving styles (e.g. intensity or duration of acceleration events) would produce statistically signi®cant di erences in measured emissions. To test this driver variability hypothesis, we conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 24 publications
(49 reference statements)
0
40
0
Order By: Relevance
“…The conversion from volume concentration of CO, HC, and NO to their fuel-specific mass emission factors E CO , E HC , and E NO may be expressed as follows 12 :…”
Section: Methods For Calculating Vehicle Emission Factorsmentioning
confidence: 99%
“…The conversion from volume concentration of CO, HC, and NO to their fuel-specific mass emission factors E CO , E HC , and E NO may be expressed as follows 12 :…”
Section: Methods For Calculating Vehicle Emission Factorsmentioning
confidence: 99%
“…5 A variety of other factors associated with realworld driving and not represented by the standard type approval tests have been found to influence emission levels including driver aggression, 6,7 road grade and auxiliary engine loads such as air-conditioning, 8 and global driving style. 9 These studies have suggested that better characterisation of emissions inventories can be estimated using on-board measurements, rather than dynamometer tests.…”
Section: Previous On-board Emissions Monitoring Studiesmentioning
confidence: 99%
“…These cycles can be found either for automotive [1]- [4] or for locomotive [5] applications. However, the use of these cycles in HEV design has been criticized since they are not truly representative of real driving conditions, specifically depending on the effect of the environment (i.e., road traffic, signalization, and driver's driving style [6], [7]). The main difficulty in finding representative profiles for driving cycles is related to their heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…The main difficulty in finding representative profiles for driving cycles is related to their heterogeneity. To overcome this problem and facilitate the identification of more realistic profiles in compliance with driving conditions, statistical studies have been performed from real-world driving cycles issued from data collected on vehicles (see [7]- [12] for example). In this context, the clustering analysis of real-world cycles has been investigated, leading to the construction of new reference cycles obtained from the concatenation of typical…”
Section: Introductionmentioning
confidence: 99%